Variants of impingement syndrome of the shoulder joint - V. A. Nesterenko; A. E. Karateev; S. V. Arkhipov; M. A. Makarov; S. A. Makarov; E. I. Bialik; V. I. Stadnik; A. D. Bimbaeva; V. E. Bialik; V. A. Zelenov; A. A. Roskidailo; E. A. Naryshkin; et al. (Научно-практическая ревматология)
Pain in the shoulder joint is one of the most common reasons for seeking medical help associated with the pathology of the musculoskeletal system. The most common disease in this area that causes chronic pain is impeachment syndrome (IS) of the rotator muscles of the shoulder. The domestic literature describes in sufficient detail surgical and conservative approaches for lesions of the shoulder joint, but there are only a few publications on the types of IS. This review is devoted to the description of all occurring types of compression of the tendons of the muscles of the rotator cuff of the shoulder joint within the framework of IS.